2007
DOI: 10.1074/jbc.m703286200
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Novel Inhibitor of Matrix Metalloprotease-13 That Reduces Cartilage Damage in Vivo without Joint Fibroplasia Side Effects

Abstract: Matrix metalloproteinase-13 (MMP13) is a Zn2؉ -dependent protease that catalyzes the cleavage of type II collagen, the main structural protein in articular cartilage. Excess MMP13 activity causes cartilage degradation in osteoarthritis, making this protease an attractive therapeutic target. However, clinically tested MMP inhibitors have been associated with a painful, joint-stiffening musculoskeletal side effect that may be due to their lack of selectivity. In our efforts to develop a disease-modifying osteoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
219
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(231 citation statements)
references
References 40 publications
8
219
0
2
Order By: Relevance
“…In contrast, selectivity data on Ilomastat (Table 1) and other broad-spectrum inhibitors reported in the literature indicate that, although potent against MMP-13 activity, the broad-spectrum inhibitors lack selectivity (3,5,33,34). The only other MMP inhibitors with selectivity comparable with that of the MMP-13 inhibitors in the present study are the class of MMP-13 inhibitors recently reported in the literature (21). Steady-state kinetics and Lineweaver-Burk plot analysis of data on our MMP-13 inhibitor ALS 1-0635 demonstrated noncompetitive (mixed) inhibition.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In contrast, selectivity data on Ilomastat (Table 1) and other broad-spectrum inhibitors reported in the literature indicate that, although potent against MMP-13 activity, the broad-spectrum inhibitors lack selectivity (3,5,33,34). The only other MMP inhibitors with selectivity comparable with that of the MMP-13 inhibitors in the present study are the class of MMP-13 inhibitors recently reported in the literature (21). Steady-state kinetics and Lineweaver-Burk plot analysis of data on our MMP-13 inhibitor ALS 1-0635 demonstrated noncompetitive (mixed) inhibition.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, our strategy for development of DMOADs was to focus on identification of highly selective allosteric MMP-13 inhibitors free of hydroxamic acid or other zinc-chelating functional groups that contribute to inhibition of multiple MMPs. The rationale for targeting MMP-13 came from 1) overwhelming data on a potential role of MMP-13 in the pathogenesis of OA (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and 2) data from studies of MMP-13 knockout mice and humans with an MMP-13 mutation, suggesting lack of MSS liability (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc metalloenzymes such as MMPs are involved in the degradation of connective tissue and cartilage breakdown [86]. Copper on the other hand has a key role in building the extracellular matrix by cross-linking proteins such as collagen and elastin to give them structural integrity [87].…”
Section: Copper Zinc and Ra And Oamentioning
confidence: 99%
“…The overlay of PDB 2OW9 and PDB 2OZR10h indicated that on the right‐hand side, HOH747, HOH813 and HOH836 can be considered as structural water molecules that can be targeted as valuable binding partners in order to improve the binding affinity of phthalimide scaffold 4 . Compared with their counterparts in PDB 2OZR, those water molecules are located at very similar positions and share the same binding motifs to the target protein: HOH747 binds to the backbone NH of Leu 164, HOH813 binds to the carboxylate side chain of Glu 202, and HOH836 binds to the catalytic zinc ion as well as to the backbone carbonyl of Pro 221.…”
mentioning
confidence: 99%